2020
DOI: 10.1088/1752-7163/ab944d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of academic stress on the levels of oral volatile sulfur compounds, halitosis-related bacteria and stress biomarkers of healthy female undergraduate students

Abstract: To investigate whether academic stress changes the salivary microbiota and its relationship with salivary parameters, evaluating the effects on the production of volatile sulfur compounds (VSCs) in healthy women. Fifty-five women who were enrolled in a four-year Dentistry course were assessed for academic stress by the questionnaire Maslach Burnout Inventory—Student Survey and were then classified into ‘Not Stressed’ and ‘Stressed’ groups. Cortisol and alpha-amylase (AA) were measured as physiological stress b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Moreover, poor oral hygiene, bacterial coating of the tongue and periodontal disorders such as gingivitis, periodontitis and caries can contribute to halitosis [ 53 ]. Malodour can also be affected by dietary habits, such as smoking, alcohol consumption, obesity, diabetes, stress and advanced age [ 54 , 55 , 56 ]. In addition, risk factors such as age and tooth decay can also lead to malodour in children [ 57 ], but it is difficult to distinguish between oral bacteria that cause odour in adolescents.…”
Section: Oral Microbiome In Periodontal Diseasesmentioning
confidence: 99%
“…Moreover, poor oral hygiene, bacterial coating of the tongue and periodontal disorders such as gingivitis, periodontitis and caries can contribute to halitosis [ 53 ]. Malodour can also be affected by dietary habits, such as smoking, alcohol consumption, obesity, diabetes, stress and advanced age [ 54 , 55 , 56 ]. In addition, risk factors such as age and tooth decay can also lead to malodour in children [ 57 ], but it is difficult to distinguish between oral bacteria that cause odour in adolescents.…”
Section: Oral Microbiome In Periodontal Diseasesmentioning
confidence: 99%
“…Bernardi et al (2019) revealed that the dorsal tongue biofilm of patients with halitosis had a significantly higher proportion of F. nucleatum and Streptococcus. In addition, in recent years, studies have revealed that psychological stress and anxiety can increase the discharge of VSCs in the oral cavity, which may be correlated with F. nucleatum (Nani et al, 2017;De Lima et al, 2020).…”
Section: Association Between F Nucleatum and Halitosismentioning
confidence: 99%
“…The factors that increase the likelihood of halitosis include periodontal diseases, dry mouth, smoking, alcohol consumption, dietary habits, diabetes, and obesity. Halitosis can also be affected by the general hygiene of the body (i.e., dehydration, starvation, and high physical exertion), advanced age, bleeding gums, decreased brushing frequency, but also by stress [3,[13][14][15][16]. Produced during stress, catecholamines and cortisol increased hydrogen sulfide production by sub-gingival anaerobic bacteria [17].…”
Section: Introductionmentioning
confidence: 99%